2007
DOI: 10.1074/jbc.m701828200
|View full text |Cite
|
Sign up to set email alerts
|

Improved Stability of the Jun-Fos Activator Protein-1 Coiled Coil Motif

Abstract: The second phase is independent of concentration and is exponential. In contrast, in the unfolding direction, all molecules display two-state kinetics. Collectively this implies a transition state between unfolded helices and dimeric intermediate that is readily traversed in both directions. We demonstrate that the added stability of cFos-JunW Ph1 relative to cFos-JunW is achieved via a combination of kinetic rate changes; cFosJunW E23K has an increased initial dimerization rate, prior to the major transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 55 publications
2
75
0
1
Order By: Relevance
“…44 Recently, we investigated the kinetics of complex formation between cFos and JunW, JunW Ph1 , and the intermediate mutants (JunW Q21R , JunW E23K ) using stopped-flow analysis. 45 This study revealed that all of the possible peptide mixtures fold via a transiently populated dimeric intermediate. Of these, cFos-JunW E23K is the only dimer where the intermediate can be detected by equilibrium denaturation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…44 Recently, we investigated the kinetics of complex formation between cFos and JunW, JunW Ph1 , and the intermediate mutants (JunW Q21R , JunW E23K ) using stopped-flow analysis. 45 This study revealed that all of the possible peptide mixtures fold via a transiently populated dimeric intermediate. Of these, cFos-JunW E23K is the only dimer where the intermediate can be detected by equilibrium denaturation.…”
Section: Discussionmentioning
confidence: 97%
“…1). 45 The probability of these two contrasting selection systems arriving at such similar sequences by chance is unfeasibly low, indicating that both systems indeed selected for similar properties. The sequence of helix JunW Ph2 differs from the sequences of JunW Ph1 and JunW especially in the hydrophobic core.…”
Section: Phage Selection and Analysismentioning
confidence: 97%
“…A further insight into the structural determinants of stability arose by dissecting the folding pathway of four c-Jun leucine zipper variants that bind with high affinity to c-Fos [24]. These encompassed a PCA-selected winner (JunW) [17], a phage-display-selected winner (JunW Ph1 ) [22] and two intermediate mutants.…”
Section: Folding Of Jun-fos Ap-1 Coiled-coil Motifsmentioning
confidence: 99%
“…Echoing an early suggestion that Fos and Jun leucine zipper domains be used as a molecular Velcro in biotechnology (53) are studies that utilized leucine zippers to verify the substrate for a tyrosine kinase (54), to facilitate the amyloid formation of ␣-synuclein (55), to enhance the interaction of different proteins in a yeast two-hybrid setup (56), and to help design synthetic leucine zipper peptides that exhibit extremely high affinity for heterodimerization (41,(57)(58)(59). This work presents a suite that incorporated Fos and Jun to solve different challenges faced in recombinant protein expression and purification.…”
Section: Discussionmentioning
confidence: 99%